Beethoven's Cello: Five Revolutionary Sonatas and Their World - Moskovitz, Marc D.; Todd, Larry R. (Suffolk Boydell & Brewer, 2017)
Beethoven's Cello is the ideal companion for cellists, pianists, musicologists and chamber-music devotees desiring a comprehensive understanding of this beloved repertoire.In 1796 the young Beethoven presented his first two cello sonatas, Op. 5, at the court of Frederick William II, an avid cellist and the reigning Prussian monarch. Released in print the next year, these revolutionary sonatas forever altered the cello repertoire by fundamentally redefining the relationship between the cello and the piano and promoting their parity. Beethoven continued to develop the potential of the duo partnership in his three other cello sonatas - the lyrical and heroic Op. 69 and the two experimental sonatas Op. 102, No. 1 and No. 2, transcendent compositions conceived on the threshold of the composer's late style.In Beethoven's Cello, Marc D. Moskovitz and R. Larry Todd examine these seminal cornerstones of the cello repertoire and place them within their historical and cultural contexts. Also addressed are the three variation sets and, in a series of interludes, the cellos owned by Beethoven, the changing nature of his pianos, the cello-centric 'Triple' Concerto and the arrangements for cello and piano of other works. Featuring a preface by renowned cellist Steven Isserlis and concluding with the reviews of the composer's cello music published during his lifetime, Beethoven's Cello is the ideal companion for cellists, pianists, musicologists and chamber-music devotees desiring a comprehensive understanding of this beloved repertoire.MARC D. MOSKOVITZ is principal cellist of the ProMusica Chamber Orchestra. He has recorded the music of virtuoso cellists David Popper and Alfredo Piatti for the VAI label, and his American premiere of Zemlinsky's Cello Sonata was heralded by the Washington Post as 'an impassioned performance'. Moskovitz has contributed to the New Grove Dictionary of Music and Musicians; and his biography, Alexander Zemlinsky: A Lyric Symphony, was published by Boydell & Brewer in 2010.Recognized as 'Mendelssohn's most authoritative biographer' (The New Yorker), R. LARRY TODD is Arts and Sciences Professor at Duke University. He is the author of Mendelssohn: A Life in Music, named Best Biography in 2003 by the Association of American Publishers, and Fanny Hensel: The Other Mendelssohn, awarded the ASCAP Nicholas Slonimsky Award for outstanding biography in music. As a pianist, he has recorded with Nancy Green the complete cello works of Mendelssohn and Fanny Hensel for JRI Recordings.
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Cello; Sonata; Musical analysis; Vienna (Austria)